Architectural Elements, Wall Paintings, and Mosaics - Lichtenberger, Achim; Raja, Rubina (Brepols, 2022)
The Decapolis city of Jerash has long attracted attention from travellers and scholars, due both to the longevity of the site and the remarkable finds uncovered during successive phases of excavation that have taken place from 1902 onwards. Between 2011 and 2016, a Danish-German team, led by the universities of Aarhus and Münster, focused their attention on the Northwest Quarter of Jerash - the highest point within the walled city - and this is the fourth in a series of books presenting the team’s final results. This two-part set offers a comprehensive presentation of Jerash’s rich building heritage from the Late Hellenistic period up to the city’s destruction in the mid-eighth century <span class=